PENGARUH HABITS OF MIND DAN SELF EFFICACY TERHADAP BERPIKIR KRITIS DI SMP NEGERI 6 KOTA BENGKULU - Juliani, Linda Yeka; Hanifah, Hanifah; Haji, Saleh (LPPM Universitas Bina Bangsa, 2024)
This study aims to investigate the influence of habits of mind and self efficacy on students' critical thinking. A quantitative approach with an ex post facto method was employed for this research. The population consisted of students from SMP Negeri 6 Bengkulu City totaling 103 students. Instruments utilized included a critical thinking test, a habits of mind questionnaire, and a self efficacy questionnaire. Multiple Linear Regression was employed for data analysis. The results indicate that habits of mind and self efficacy significantly and positively influence critical thinking. The independent variables, habits of mind and self efficacy, explained 26.2% of the variation in the dependent variable, critical thinking, while the remaining 73.8% was influenced by factors not included in the study model